PENERAPAN METODE CPM DAN PERT PADA PT. XYZ DALAM PEMBANGUNAN PROYEK APARTEMEN GARDEN DI TANGERANG - Prihandoko, ST, MM, Danang; Klinzabilal, Tesar; Rifqi, Teuku Muhammad; Ezki, Vior (STIE Ekuitas, 2022)
Growth property business in Indonesia since the last years has been growth significantly; it’s marked by the increase of property prices in Indonesia due to 2017. PT XYZ is one of company engaged in property business or real estate. At this time PT XYZ was currently conducting project development for Apartement located in Alam Sutera, Tangerang. The purpose of this research is to find out the application of the Critical Path Method and PERT method that can be applied to the apartment project, to compare the costs before and after using the Critical Path Method and PERT method, to determine the effectiveness and efficiency of using Crashing Program on the Apartment project. To optimize the development project, Therefore, they need a mature and structured Project Management to finish project to avoid delay. Hence, researchers tried to apply a method that approach optimization by using the Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT) in Project Management, to be able to maximize profit and reduce the risk loss for the company and consumers.